Patterns of biofilm structure and formation kinetics among Acinetobacter baumannii clinical isolates with different antibiotic resistance profiles. Issue 1 (27th October 2015) - Dahdouh, E.; Orgaz, B.; Gómez-Gil, R.; Mingorance, J.; Daoud, Z.; Suarez, M.; San Jose, C.
Abstract : This study evaluates the rates of biofilm formation in light of the different characteristics of twelve A. baumannii clinical isolates. Abstract : Acinetobacter baumannii is a ubiquitous organism that has been involved in a wide range of nosocomial infections. Its ability to produce biofilms, among other characteristics, allows it to persist in hospitals for prolonged periods. In this study, in order to check the possible relationship between its resistance to different antibiotics and its ability to form biofilms on inert surfaces, the rate of biofilm formation as well as siderophore production and detection of OmpA and CsuE by PCR were investigated for 12 A. baumannii clinical isolates. The biofilms were cultured at 37 °C on steel coupons immersed in BHI broth and the attached viable cells were counted after 5, 24 and 48 h. Confocal Laser Scanning Microscopy (CLSM) images were obtained for some of the strains that were noted to produce a brown pigment. The biofilm volume and substratum coverage were estimated with an image analysis software program. Our data, though preliminary, show that the quicker biofilm formers were strains susceptible to aminoglycosides, whereas the biofilms providing thicker and more uniform surface coverage were produced by carbapenem-resistant strains, producing a brown pigment with a plausible siderophore role. Further investigation into a wider set of isolates could help better understand the relationship between biofilm formation and various clinical findings.